Analysis of the Decision to Use Jastip (Personal Shopper) through Trust as a Mediating Variable - Brahmana, Selvina Tawanta; Shiratina, Aldina (Journal of Sustainable Economic and Business, 2024)
Objectives: In the digital era, the phenomenon of "jastip" or personal shopping has become a popular choice for online shopping. However, consumer trust in this service is often disrupted by cases of fraud, which in turn affects users' decisions. Methodology: The population of this study consists of users of Jastip (Package Delivery Service) in the Jabodetabek area. The data collection method used is purposive sampling with a total of 240 respondents. Data analysis was performed using SEM-PLS. Conclusion: The results show that Reputation and Service Quality have a positive and significant effect on Trust, while Social Media Marketing has a positive but insignificant effect on Trust, and Trust has a positive and significant effect on the Decision to Use